Berberine Improves Benign Prostatic Hyperplasia via Suppression of 5 Alpha Reductase and Extracellular Signal-Regulated Kinase in Vivo and in Vitro - Youn, Dong-Hyun; Park, Jinbong; Kim, Hye-Lin; Jung, Yunu; Kang, JongWook; Lim, Seona; Song, Gahee; Kwak, Hyun Jeong; Um, Jae-Young (Frontiers in Pharmacology, 2018)
Benign prostate hyperplasia (BPH) is a common disease in elderly men, characterized by proliferated prostate and urinary tract symptoms. The hormonal cascade starting by the action of 5 alpha reductase (5AR) is known to be one of the pathway responsible for the pathogenesis of BPH. Present investigation evaluated the capacity of berberine (BBR), a nature-derived compound abundant in Coptis japonica, in testosterone-induced BPH rats. Experimental BPH was induced by inguinal injection with testosterone propionate (TP) for 4 weeks. BBR or finasteride, a 5AR inhibitor as positive control, was treated for 4 weeks during BPH. BPH induced by TP evoked weight gaining and histological changes of prostate and BBR treatment improved all the detrimental effects not only weight reduction and histological changes but also suppression of prostate specific antigen (PSA), which is elevated during BPH. Additionally, BBR suppressed TP-associated increase of 5AR, androgen receptor (AR) and steroid coactivator-1 (SRC-1), the key factors in the pathogenesis of BPH. To evaluate the underlying molecular mechanisms responsible for beneficial effects of BBR, we investigated whether these effects were associated with the mitogen-activated protein kinase (MAPKs) pathway. BPH induced by TP showed increased phosphorylation of extracellular signal-regulated kinase (ERK), whereas this was suppressed by BBR treatment. On the other hand, c-Jun-N-terminal kinase (JNK) and p38 mitogen-activated protein kinase (p38) was not changed in BPH rats. In in vitro study using RWPE-1 cells, a human prostate epithelial cell line. TP increased cell proliferation and BPH-related key factors such as PSA, AR and 5AR in RWPE-1 cells, and those factors were significantly decreased in the presence of BBR. Furthermore, these proliferative effects in RWPE-1cells were attenuated by treatment with U0126, an ERK inhibitor, confirming BBR can relieve overgrowth of prostate via ERK-dependent signaling. The cotreatment of U0126 and BBR did not affect the change of 5AR nor proliferation compared with U0126 alone, suggesting that the effect of BBR was dependent on the action of ERK. In conclusion, this study shows that BBR can be used as a therapeutic agent for BPH by controlling hyperplasia of prostate through suppression of ERK mechanism.